Pemodelan Sebaran Konsentrasi Nitrat di Kawasan Pelabuhan Perikanan Nusantara Jembrana, Bali - Hulu, Pilipus; Nurweda Putra, I Dewa Nyoman; Darmendra, I Putu Yogi; Fajar Maharta, I Putu Ranu (Journal of Marine Research and Technology; Vol 8 No 1 (2025): FEBRUARI 2025, 2025)
The water area of the Perikanan Nusantara Port (PPN) Jembrana, Bali, is an area affected by environmental conditions, including nitrate concentrations. Previous studies have shown that nitrate concentrations in these waters have exceeded the quality standard set in Bali Governor Regulation No. 16 of 2016 by 0.008 mg/l. However, the study only discussed nitrate concentrations in two conditions, namely during high tide and low tide. Therefore, further research is needed to analyze nitrate concentrations in four tidal conditions, namely high tide, tide to low tide, low tide, and low tide to high tide. This study used numerical modeling method with Finite Volume Coastal Ocean Model (FVCOM) approach in 2-D scale. The modeling was conducted in two stages: first, running the hydrodynamics numerical modeling, and second, running the European Regional Seas Ecosystem Model (ERSEM) numerical modeling. The modeling results show that the movement pattern of ocean currents in port waters is dominated by the influence of tides and port bathymetry. The current velocity of each condition has minimum, maximum and average values of 0.001 m/s, 0.555 m/s, and 0.131 m/s, respectively. The nitrate distribution pattern shows concentrations that tend to be high in the harbor pond area, with a minimum concentration of 0.112 mg/l and a maximum of 0.570 mg/l. The distribution of nitrate concentration is thought to be influenced by biological processes in the water, such as decomposition and the presence of phytoplankton, as well as by ocean currents and other physico-chemical parameters, such as temperature, salinity, dissolved oxygen (DO), pH, and depth. Compared to previous studies, the nitrate concentration found in this study was lower, but still exceeded the threshold set by the government.